Percutaneous Trans-Mitral Commissurotomy in the Contemporary Era, Real Time Experience and a Retrospective Analysis - Wesam A. Alhejily (Journal of King Abdulaziz University: Medical Sciences, 2023)
Rheumatic mitral stenosis is a rare disease nowadays. In the Kingdom of Saudi Arabia and at King Abdulaziz University Hospital, we still see annually a few cases of advanced cases of rheumatic mitral stenosis among adult patients requiring hospital admission and urgent interventional treatment. We opt to study retrospectively the clinical presentation, techniques, outcomes, complications, and predictors of mortality related to percutaneous balloon intervention in patients with symptomatic mitral stenosis who were treated at King Abdulaziz University Hospital between 2009 and 2015. Among 6536 adult admissions over a 6-year time period, there were 21 new cases of symptomatic, echo-confirmed mitral stenosis (3/1000); only 6 cases (28.6%) were eligible for intervention. In the intervention group the mean age was 38; 83% were female; 50% Non-Saudi. In five (83%) out of six cases balloon valvuloplasty had increased mitral valve area by 0.596 ± 0.312 and reduced the mean mitral valve gradient by 6 ± 3.847 (p = 0.05 and 0.012, respectively). The most important predictor of successful dilation to valve area above 1.5 was Wilkin’s score. Two indirect deaths occurred in a 6-month follow-up period and were correlated to age of 45 and above with initial presentation of either stroke, or pulmonary hypertension (mean pulmonary artery pressure > 45) and refractory heart failure.